Pendampingan Pembelajaran Mobile Learning Kepada Organisasi Himpunan Masyarakat Mamberamo Tengah dengan Menggunakan Aplikasi Thunkable - Melda Agnes Manuhutu; Jihan Jihan; Janet Janet; Alex Karoba (Lembaga Pengembangan Kinerja Dosen, 2025)
Developments in the digital era require communities to have the ability to access, understand, and utilize technology as part of their preparedness for global change. However, not all community groups have equal access and digital skills, particularly regional communities such as the Central Mamberamo Community Association (HMMT) in Sorong City. This community service activity aims to empower members of this community through training in developing mobile learning-based digital teaching materials using the Thunkable application. The method used was a direct, participatory, project-based approach, allowing participants to be actively involved in every stage of the activity. The results of the activity showed an increase in participants' understanding of the concept of mobile learning, their ability to use the Thunkable platform, and the creation of simple teaching material prototypes relevant to the local context. The training also succeeded in increasing learning motivation and a sense of ownership of the developed digital products. These findings support the effectiveness of no-code and project-based learning approaches in improving digital literacy in non-technological communities. This activity serves as an initial model for inclusive and sustainable technology-based community empowerment. Furthermore, this activity also had a positive impact on strengthening collaboration among HMMT community members. By working together in teams, participants not only improved their technical skills but also developed more effective collaboration and communication skills. Using the no-code Thunkable app allows them to create digital learning materials without requiring a deep technical background, making them more accessible to a wide range of communities. The success of developing a prototype of learning materials tailored to local needs also opens up opportunities for the community to continue developing their digital products in the future, with the hope of expanding access to more equitable and quality education in the region.